FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MEWUJUDKAN APARATUR DESA YANG BERSIH DARI KKN DI DESA CUKAN LIPAI KECAMATAN BATANG ALAI SELATAN KABUPATEN HULU SUNGAI TENGAH - Habibah Fiteriana (JOURNAL OF ISLAMIC AND LAW STUDIES, 2022)
AbstractThis research was compiled based on the existence of asymmetry between the implementation of the functions of the Village Consultative Body in Cukan Lipai Village as stated in Law Number 6 of 2014 with fact in the field. This is because the government in the village is filled with people recruited by the village head from the relatives and the success team during the village head election without strict selection and consideration. The purpose of this study was to determine the performance of the implementation of the function of the Village Consultative Body in Cukan Lipai Village in realizing a village apparatus that was clean from corruption, collusion and nepotism and obstacles to its implementation.This research is an empirical legal research that is descriptive qualitative and located in Cukan Lipai Village, Batang Alai Selatan District, Hulu Sungai Tengah Regency. The results showed that the performance of the implementation of the functions of the Village Consultative Body was still not effective due to a lack of understanding of the functions of the Village Consultative Body. The village head and village apparatus take many roles in the policies issued by the Village Consultative Body. So that the presence of the Village Consultative Body as the supervisor of the performance of the village head which is expected to play a role in realizing a village apparatus that is free from corruption, collusion and nepotism is nil.Â Keywords: Function, Village Consultative Body, Village Apparatus, Corruption Collusion and Nepotism.